Efektivitas Pelaksanaan Supervisi Akademik Pengawas Dalam Meningkatkan Kompetensi Profesional Guru PAI SD di Kecamatan Tambun Selatan - Fajar Azzam Pasha Akhmad (PARAMETER, 2022)
Effective strategy of academic supervision by supervisors can improve the professional competence of teachers. The limited number of supervisors and the extent of the target area are problems in the academic supervision. This study aims at knowing: 1) the effectiveness of academic supervision by supervisors to improve the professional competence of Islamic education teachers at the elementary school in District Tambun Selatan 2) the constraints faced by supervisors in conducting academic supervision, and the solution for supervisors of academic supervision that can improve the professional competence of Islamic education teachers at the elementary school in District Tambun Selatan. The results show that: 1) academic supervision conducted by supervisors in Islamic education is effective to improve the profesional competence of Islamic education teachers at the elementary school. It can be seen from the increasing in mastery of teaching materials, instructional planning, implementation of learning and assessment of learning outcomes. 2) The barriers experienced by supervisors in academic supervision in Islamic education is a lack of supervisory personnel, the number of teachers that should be supervised, the lack of intensity of supervision and the lack of competence development of supervisors in Islamic education. 3) The solution of these problems are the recruitment of new supervisors, increasing the intensity of supervision at classroom visits and increasing capacity-building programs of academic supervision for supervisors regularly and continuously. Abstrak Strategi supervisi akademik pengawas yang efektif dapat meningkatkan kompetensi profesional guru. Keterbatasan jumlah pengawas dan luasnya wilayah binaan merupakan persoalan dalam supervisi akademik. Penelitian ini bertujuan mengetahui: 1) efektivitas supervisi akademik pengawas dalam meningkatkan kompetensi profesional guru PAI SD di Kecamatan Tambun Selatan, 2) kendala yang dihadapi pengawas dalam melakukan supervisi akademik, dan solusi agar supervisi akademik pengawas dapat meningkatkan kompetensi profesional guru PAI SD di Kecamatan Tambun Selatan. Hasil penelitian menunjukkan bahwa: 1) supervisi akademik yang dilakukan pengawas Pendidikan Agama Islam cukup efektif dalam meningkatkan Kompetensi profesional guru PAI terlihat dari meningkatnya penguasaan materi bahan ajar, perencanaan pembelajaran, pelaksanaan pembelajaran dan penilaian hasil belajar. 2) Hambatan yang dialami pengawas dalam supervisi akademik adalah kurangnya tenaga pengawas PAI, banyaknya guru yang harus dibina, kurangnya intensitas supervisi dan kurangnya pengembangan kompetensi supervisi akademik pengawas PAI. 3) Solusi dari kendala tersebut adalah rekrutmen pengawas baru, peningkatan intensitas supervisi kunjungan kelas dan peningkatan program pembinaan kemampuan supervisi akademik pengawas secara berkala dan berkesinambungan.